Effects of different footwear properties and surface instability on neuromuscular activity and kinematics during jumping - Lesinski, Melanie; Prieske, Olaf; Borde, Ron; Beurskens, Rainer; Granacher, Urs (Journal of strength and conditioning research, 2018)
The purpose of this study was to examine sex-specific effects of different footwear properties vs. barefoot condition during the performance of drop jumps (DJs) on stable and unstable surfaces on measures of jump performance, electromyographic (EMG) activity, and knee joint kinematics.